Prevalence of Anxiety and Depression in Breast Cancer Patients and their Correlation with Socio-Demographic Factors - Dadheech, Apoorva; Kumawat, Suman; Sharma, Deepesh; Gothwal, Ravinder Singh; Dana, Rohitashwa; Meena, Chetna; Saini, Naresh Kumar (Asian Pacific Journal of Cancer Care, 2023)
Background and objective: Being diagnosed with breast cancer or undergoing surgery, radiation, or chemotherapy as a treatment modality is often experienced as a traumatic event for many women. This emotional distress can negatively impact their quality of life and compliance with treatment, ultimately increasing the risk of mortality, which is considered the sixth vital sign in cancer care. The aim of this study was to estimate the prevalence of depression and anxiety in breast cancer patients and examine their correlation with socio-demographic factors. Materials and Methods: A cohort of 140 breast cancer patients registered in the Department of Radiation Oncology, SMS Medical College, Jaipur, between January 2022 and December 2022, was recruited. Participants were interviewed using a structured questionnaire that included socio-clinical and demographic factors, as well as the PHQ-2 and GAD-2 scales. Results: The prevalence of depression among patients was 37.9% (53/140), and approximately one-third (33.6%, 47/140) of cases exhibited symptoms of anxiety. The majority of cases had stage III breast cancer (69.3%, 97/140), followed by stage II (16.4%, 23 cases) and stage IV (14.3%, 20 cases). Factors such as place of residence, educational status, employment status, accompanying person, and marital status emerged as significant predictors of depression risk. Additionally, age group, marital status, and financial status showed a statistically significant association with elevated anxiety symptoms. Conclusion: This study highlights a high prevalence of anxiety and depression among breast cancer patients, with higher vulnerability observed in patients from rural areas, those who are single, have low monthly income, belong to a younger age group, and have a lower education level. Therefore, special care, support, and possible referral to the psychiatry department may be necessary for these patient groups.